Graphics design work: event / Sharifah Aishah Wan Omarshah - Wan Omarshah, Sharifah Aishah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The project focuses on rebranding Sarawak's tourist attractions, particularly a music event called Borneo Music Festival Live (BMFL) in 2022, featuring various genres including Traditional Sarawak music, Electric Dance Music, and pop. A specific theme, that blends sci-fi and brutalism, will create a firm logo to overcome the design challenges. This will strengthen BMFL’s brand identity and image in their corporate design, expanding emotional connections through diverse collateral and visually compelling elements through digital multimedia.